EFFICIENCY MEASUREMENT IN THE AGRICULTURAL SALES COOPERATIVE UNIONS VIA DEA: A CASE STUDY IN MARMARABİRLİK (Third Sector Social Economic Review, 2017)
Cooperatives are one of the locomotives of cultural and economic development and have an important role in the implementation of social state policies. Cooperatives operate in banking and insurance, agriculture, wholesale and retail trade, manufacturing, residential construction, water, electricity, animal husbandry, healthcare sectors and many other sectors. In many countries of the world, it is aimed to keep the sustainability of the activities of the cooperatives in the foreground by giving public support to the cooperatives. It is seen that there are many cooperative types operating in various fields. Agricultural sales cooperative unions receiving olive and olive oil are one of them. The keep continuing activities of agricultural sales cooperative unions receiving olive and olive oil are very important in terms of agricultural, rural, social and economic development. Efficiency measurement in co-operatives is important for the sustainability of the activities of cooperatives. In this study, it was aimed to determine the efficiency level of Marmarabirlik, which is one of the agricultural sales cooperatives unions receiving olive and olive oil, using the DEA method. For this purpose efficiency was measured for a total of eleven years between 2006 and 2016 for Marmarabirlik. Each year was taken as a desicion making unit. The input-oriented CCR model was used in the study. As a result of the analyses made, Marmarabirlik was found to be efficient in the years having efficiency scores of 1 (100%) and inefficient in other years having efficiciency scores lower than these values.
Keywords: Efficiency Measurement; Cooperative; Data Envelopment Analysis; Olive; Olive Oil.